THE WORLD WITHIN: TEACHING IN A SAFE AND ENDURING SCHOOL ENVIRONMENT - Creensanita D. Damiao; Geronimo S. Obaob (European Scientific Journal, ESJ, 2014)
Understanding the vital role of the learning environment, this chapter aims at identifying on whether or not teacher’s work place has been safe. It also aims to reveal whether teaching effectiveness correlates with safe work place. It is found out that the secondary teachers could effectively work better if the teaching environment is safe and conducive as revealed when these variables were correlated. Teaching effectiveness could be equated with safety in the workplace. Teachers could provide a better and more efficient delivery of instruction if they are teaching in a very ideal classroom even if their teaching assignment is far from their residence. A safe workplace was perceived by the teacher respondents as an important factor in the overall quality of work life among secondary public school teachers as it was found out to have a significant impact in effective instruction delivery. It even showed an impact factor on the teachers’ quality of work life because majority of the teachers were residing near to the school where they are teaching and that most of them were teaching in a school where buildings are well – maintained. This showed therefore that security and safety in their work is still properly managed and that teachers’ quality of work life is evident.